Method to analyse and quantify the propensity of hair dyes to desorb from human hair fibre - Kristina Hetherington; Alenka Tidder; Bethany J. Tack; Meryem Benohoud; Dan Nowlan; Anwar Zahar; Xiaoguang Li; Darcy Prater; Jeanna C. Zguris; Tanu Tokle; Christopher M. Rayner; Richard S. Blackburn (Heliyon)
Background: The use of hair dyes to alter the aesthetics of human hair is a very popular consumer habit. Dyes and their precursors used in hair coloration have been investigated for safety both in terms of exposure of consumers during the dyeing process, and afterwards in rinse water. However, few analytical methodologies exist that provide understanding of the dye desorption process and are able to relate this to visible colour change on the hair. There are also limited quantitative methods for evaluating morphologically different hair types, and the colour changes that occur during the life of the colorant on the user. Results: Herein, we describe a method of back-extraction of a two-component dye system from morphologically different hair types. Through screening of common back-extraction methods used in analysis of dyed textile artefacts, a new back-extraction methodology has been developed and adapted for application on dyed hair using a 2:1 (v/v) water:pyridine solvent system. By separation of extracted compounds with high liquid pressure chromatography, quantitative data on the amount of dye removed are obtained, representing the first application of such methodology in analysing hair dyes. Significance and novelty: For the first time, an analytical method is provided that can directly relate dye molecule desorption from hair with visual colour loss quantified by spectrophotometry. Moreover, it has been demonstrated that these techniques are applicable to morphologically different hair types, including those with significant underlying natural pigmentation.